An Efficient and Green Method for Synthesis of 2, 4, 5-Triarylimidazoles without Use of Any Solvent, Catalyst, or Solid Surface. (10th December 2013) - Samanta, Swati; Sarkar, Saheli; Pal, Rammohan; Mallik, Asok K.
Abstract : An efficient and green method for synthesis of 2, 4, 5-triarylimidazoles without use of any catalyst or solvent has been developed simply by heating (at 130°C) of mixtures of 1, 2-diketone, aromatic aldehyde, and ammonium acetate in 1 : 1 : 3 mole ratio.